Connections Between Vitamin D Deficiency and Brain Structural Changes: Implications for Neurocognitive Function and Neurodegenerative Disorders - Ryden, Patcharin (Biomedical Sciences and Clinical Medicine, 2023)
In the general world population, vitamin D insufficiency frequently occurs. Severe vitamin D deficiencies are more common in individuals who also have critical illnesses. Ultraviolet B (UVB) radiation applied to the skin has an impact on the production of vitamin D. Through its anti-inflammatory and anti-autoimmune effects, vitamin D plays an immunomodulatory role. The regulation of calcium-mediated neuronal excitotoxicity, the decrease of oxidative stress, the induction of synaptic structure proteins as well as inadequate neurotransmitters and neurotrophic factors are all aspects of how vitamin D functions in the nervous system. A lack of dietary consumption and inadequate sun exposure can cause vitamin D deficiency. Vitamin D is essential for preserving brain health and function. Vitamin D deficiency can worsen the neurocognitive effects of disorders like Parkinson’s disease, Alzheimer’s disease, and other dementias. Mild cognitive impairment (MCI) refers to the earliest stage of memory impairment or other cognitive function loss. It has been found that the volume of the hippocampus and white matter integrity are both on the decline which is related to this cognitive impairment. There has been only limited exploration of the brain-specific areas that undergo structural change in response to vitamin D status. The objective of the present article was to review the connections between vitamin D deficiency and structural changes in the brain including implications for neurocognitive and neurodegenerative disorders in order to provide additional understanding, especially of brain areas that are involved with neurocognitive functioning or neurodegenerative disorders.